Grid-enabling a vibroacoustic analysis toolkit. (21st October 2008) - Bentow, Brian; Dodge, Jonathan; Homer, Aaron; Moore, Christopher D.; Keller, Robert; Lee, Craig; Thomas, Mark; Presley, Matthew; Seidel, Jorge; Davis, Robert; Betser, Joseph
A vibroacoustic analysis toolkit for launch vehicle telemetry was refactored as a service architecture using Globus Toolkit 4.0. We grid-enabled two tools in the analysis flow, managing their remote execution workflow from a desktop client. We examine the performance of the tools and the processing time for the entire tool chain. The results indicate that coordinated communication and execution scheduling as part of workflow management can significantly improve overall efficiency. Our experience also shows that the service-oriented architecture approach, using grid computing tools, can provide a more flexible system design, in addition to improved performance and increased utilisation of resources.